2009
DOI: 10.1016/j.ymeth.2008.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biophysical analyses of concerted (U5/U3) integration

Abstract: Retrovirus integrase (IN) integrates the viral linear DNA genome (~10 kb) into a host chromosome, a step which is essential for viral replication. Integration occurs via a nucleoprotein complex, termed the preintegration complex (PIC). This article focuses on the reconstitution of synaptic complexes from purified components whose molecular properties mirror those of the PIC, including the efficient concerted integration of two ends of linear viral DNA into target DNA. The methods described herein permit the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…We have observed that HIV IN purified in the presence of 1 mM EDTA and 10 mM MgSO 4 in a HEPES buffer (pH 6.8)(11, 19) is a monomer in solution and is converted to a tetramer in the presence of Zn ++ (Figure 2). IN was concentrated to 15 μM (as monomers) by an ultrafiltration device and applied to a Superdex 200 column.…”
Section: Resultsmentioning
confidence: 99%
“…We have observed that HIV IN purified in the presence of 1 mM EDTA and 10 mM MgSO 4 in a HEPES buffer (pH 6.8)(11, 19) is a monomer in solution and is converted to a tetramer in the presence of Zn ++ (Figure 2). IN was concentrated to 15 μM (as monomers) by an ultrafiltration device and applied to a Superdex 200 column.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant wt HIV IN (pNY strain) 9; 48 and IN possessing the single N155H drug-resistant mutation were used in this study. Proteins were expressed in Escherichia coli BL21(DE3) cells and purified to near-homogeneity 48.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were expressed in Escherichia coli BL21(DE3) cells and purified to near-homogeneity 48. Purified IN (pNY) was used unless indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen-bonds are shown by a dashed line. The in vitro retroviral concerted integration assay has been previously described for ASLV by others (Aiyar et al, 1996;Grandgenett, 2000, 2003;Grandgenett et al, 2009;Hindmarsh et al, 1999Hindmarsh et al, , 2001Vora et al, 2004;Vora and Grandgenett, 2001) and by us (Moreau et al, 2003(Moreau et al, , 2004(Moreau et al, , 2009 as well as for HIV-1, Simian Immunodeficiency Virus (SIV) and PFV. Briefly, the system is composed of a linear donor DNA (D), a plasmid acceptor DNA, and recombinant IN.…”
Section: Effects Of In Mutations On Concerted Dna Integrationmentioning
confidence: 99%